Determinación del aporte de los sistemas agroforestales con cacao a las familias productoras, en cinco municipios en los departamentos de Cortés y Yoro, Honduras - Martínez Martínez, Carlos Armando (2015)
The data for this study was obtained from 34 cocoa plots in agro forestry systems, situated in five municipalities in the departments of Cortes and Yoro in north western Honduras. The purpose was to generate information and create a valuable socioeconomic database to determine the economic impact of agro forestry systems in small and medium size families in rural areas.The methodology used consisted of a field inventory in agro forestry systems and a questionnaire applied to farm owners or persons in charge of the farms. The results of the field assessment determined the number of tree species associated in each farm. The agro forestry systems presented variability in their floristic composition due to topographic and altitude conditions as well as size of farms among others. The field inventory tallied a total of 110 forest and shrub tree species used as shade associated with the cocoa parcels. These trees and shrub species were found to be in different frequencies and their uses vary from timber, fruit trees, firewood or other commercial forest products. The inventory found that 89% of the agro forestry systems had timber species associated with cocoa production. From an economic standpoint the timber presents a guaranteed future source of income for rural families.